ANALYSIS OF OPPORTUNITIES FOR GENERAL METHOD FOR COVERAGE OF STANDARDS HIGH-PRECISION CLOCK TIME AND FREQUENCY WITHIN SIGHT - Koval, Yu. A.; Kostyria, O. O.; Obelchenko, V. V.; Bondar, Ye. Yu.; Ivanova, Ye. O.; Yermolayev, Ye. P.; Miliakh, M. V. (Radio Electronics, Computer Science, Control, 2008)
The analysis of opportunities of a “common view” method for precision synchronization of standards of time and frequency on radio channels of direct visibility. The expediency of use for measurement of shift of time scales and frequencies correlation processing of signals is appreciated. The opportunity of use of television signals for realization a “common view” method is analyzed.